IPhone application development for dummies - Goldstein, Neal (John Wiley & Sons, 2012)
Start building iPhone apps today with this friendly guide, now in full color! Whether you're a beginning programmer who wants to build your first app or a professional developer looking to leverage the marketing power of the iPhone SDK, this book will help. It walks you through the basics for building a variety of iOS applications using Apple developer tools and covers the essential steps for creating apps that get accepted into the App Store. This new edition covers all the latest information, including key updates to iPad universal code and tips on developing specifically for mobile apps. Full-color illustrations make it easier to see exactly what will appear on your screen.* Walks you through the fundamentals of developing a variety of applications for the iPhone@* Shows you how to use Apple's developer tools@* Delves into getting your apps into the App Store and selling them@* Addresses the universal code feature that allows you to develop apps and port them from the iPhone to the iPad and back@* Covers the latest updates for the iPad universal code and the new iPhone SDK No matter what your level of expertise may be, you'll be able to leverage the power of the iOS SDK with the advice in this full-color book.
Keywords: iPhone (Smartphone) -- Programming; Mobile computing; Application software -- Development; iPhone (Téléphone intelligent); Programmation; Informatique mobile; Logiciels d'application; Développement; COMPUTERS; Programming; Microsoft Programming; Application software; Development